A possible role for essential amino acid supplementation in improving functional recovery and reducing the risk for malnutrition in COVID-19 patients - Serra, Vincenza; PAce, Fabio; Contessi, Marzia; Lampugnani, Claudia; Invernici, Giuliana; Spedicato, Francesca; Tedeschi, Alberto; De Stefano, Fabio (Progress in Nutrition, 2024)
Background and aim. In patients with severe forms of coronavirus disease-19 (COVID-19), prolonged hospitalization and immobilization decrease muscle mass and increase the risk of malnutrition. Moreover, catabolic molecules such as interleukins (IL)-1 and -6 and tumor necrosis factor (TNF) contribute to the reduction of body mass, increasing the risk of sarcopenia. Since sarcopenia represents a negative prognostic factor in COVID-19 patients, protein and/or essential amino acid (EAA) supplementation has been recommended in these patients, to counteract the loss of muscle mass and strength. Aim of this study was to evaluate the effects of a six-month dietary intervention (including a standardized protein intake and a supplementation of free EAAs) on risk of malnutrition, body composition, muscle strength and physical performance in 74 COVID-19 patients after discharge. Methods: All subjects received a balanced diet according to ideal BMI, with protein intake of 1.2 -1.5 gr/kg/day. Each participant received a supplementation of EAAs twice a day during the first three months and once daily for the remaining period. Anthropometric measurements, and assessment of muscular strength, body composition and physical performance were performed during three different visits: immediately after the hospital discharge, after three months and at the end of the six-month observation period. Results: Significant changes in body mass index (BMI), Malnutrition Universal Screening Tool (MUST) score, arm circumference and triceps fold values were observed, as well as a significant increase in total body water (TBW), and significant improvements in the S and T scores and in the short physical performance battery (SPPB) score. Conclusions: these results suggest that in patients recovering from SARS-Cov2 infection, the dietary intake of 1.2-1.5 gr per kg of protein per day associated with EAA supplementation may contribute to BMI improvement and functional recovery, reducing the risk of malnutrition and osteosarcopenia.